Control of vitamin A deficiency and xerophthalmia : report of a Joint WHO/UNICEF/USAID/Helen Keller International/IVACG, Meeting held in Jakarta from 13 to 17 October 1980 - World Health Organization; WHO; UNICEF; USAID; Helen Keller International; IVACG (Geneva : World Health Organization, 1982)
1. Introduction -- 2. Recent advances in the biochemistry of vitamin A and carotenoids -- 3. Interrelationships of vitamin A deficiency, protein-energy malnutrition and infections -- 4. Assessment of vitamin A status -- 5. Global occurrence of vitamin A deficiency and xerophthalmia -- 6. Treatment and prophylaxis schedules -- 7. Control of vitamin A deficiency and xerophthalmia -- 8. Research -- 9. References
1. Introduction -- 2. Recent advances in the biochemistry of vitamin A and carotenoids -- 3. Interrelationships of vitamin A deficiency, protein-energy malnutrition and infections -- 4. Assessment of vitamin A status -- 5. Global occurrence of vitamin A deficiency and xerophthalmia -- 6. Treatment and prophylaxis schedules -- 7. Control of vitamin A deficiency and xerophthalmia -- 8. Research -- 9. References
Keywords: Control of vitamin A deficiency and xerophthalmia